Faktor yang Mempengaruhi Peran Guru Pendidikan Agama Islam dalam Kegiatan Sosial Keagamaan di Kecamatan Payakumbuh Barat - Ikhsan, Muhamad; Wirdati, Wirdati (TSAQOFAH, 2025)
This study aims to describe and analyze the role of Islamic Education (PAI) teachers in religious social activities in Payakumbuh Barat District, focusing on how PAI teachers carry out their roles within the community both directly and indirectly, as well as the supporting and inhibiting factors affecting their performance. This research employs a qualitative method with a case study approach, using data collection techniques such as observation, interviews, and documentation. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing, with data validity tested using source triangulation. The findings show that PAI teachers make tangible contributions to the community's religious social activities, encompassing ten roles based on Djamarah's theory: corrector, inspirator, informant, organizer, motivator, initiator, facilitator, guide, demonstrator, and mediator. Supporting factors include community support and a religious environment, while inhibiting factors involve time constraints and administrative burdens. School and government policies also play a role, with varying views among PAI teachers regarding the scope and legitimacy of their roles beyond the classroom. These findings highlight the importance of strengthening synergy between educational institutions, the community, and government bodies to support the strategic role of PAI teachers in fostering religious development within society.